High-Response Identifiable Gas Sensor Based on a Gas-Dielectric ZnPc Nanobelt FET - Song, Zhiqi; Tang, Qingxin; Tong, Yanhong; Liu, Yichun (IEEE electron device letters, 2017)
Gas sensors based on organic semiconductor have recently attracted much attention due to their inherent advantages, especially excellent flexibility and good selectivity. However, the gas species identification with high sensing response remains a key subject for organic gas sensors. Herein, a ZnPc single nanobelt field-effect transistor with the gas dielectric was fabricated and exhibited excellent gas sensing performance at room temperature. The sensors show the high response with 220% to 10 ppm NO 2 and 3566% to 20 ppm H 2 S, and the low detection limit down to 50 ppb towards NO 2 /H 2 S, which surpass most reported room-temperature organic-based NO 2 /H 2 S sensors. Further, our single device realized accurate gas selective identification among NO 2 , SO 2 and H 2 S with 92% success ratio in LDA feature space.